(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Background: Regular sauna exposure has been shown to positively influence clinical symptoms in various pathologies. The purpose of this review is to present the evidence accumulated so far in order to evaluate the efficiency, effects, benefits and risks of sauna therapy in the field of various pathologies that require medical rehabilitation. Methods: A literature search was conducted on Publons and PubMed databases from January 2000 onwards. The studies selected for this review included research in humans undergoing repeated sauna sessions with at least one reported health outcome. Results: Constant application of sauna therapy has visible effecta on improving cardiac activity, endothelial function, myocardial perfusion, ventricular arrhythmia. Sauna treatment is a safe procedure for patients with cardiovascular, respiratory, musculo-skeletal pathologies, with no notable side-effects. Conclusions: Sauna therapy has proved its effectiveness in medical rehabilitation treatment starting from the musculoskeletal system and skin to the nervous system. In addition, it brings a significant improvement in the quality of life of patients. Keywords: sauna bathing; dry sauna; regular sauna exposure; clinical applications sauna; biological effects sauna; quality of life